Induction of Ovulation in Mangalarga Marchador Mares by hCG or GnRH - Ferreira-Silva, José Carlos; Nascimento, Pábola Santos; Moura, Marcelo Tigre; Basto, Sarah Romini Lima; Azevedo, Marlon Vasconcelos; Rocha, Jorge Motta; Santos Filho, José Pompeu; Oliveira, Marcos Antonio Lemos (Acta Scientiae Veterinariae, 2018)
Background: Induction of ovulation is a key procedure for horse assisted reproduction technologies, such as for artificial insemination (AI) and embryo transfer. The application of hCG remains as the primary ovulation-inducing agent for horse assisted reproduction, but alternatives are in demand to avoid its adverse effects, such as loss of ovulation-inducing efficiency over multiple applications by hCC-antibody production. Despite reports on alternative ovulation-inducing agents, pair-wise comparisons of such agents under similar conditions have been limited. Under such scenario, the work was aimed to determine the efficiency of both hCG and Buserelin at inducing ovulation in Mangalarga Marchador mares raised in the Northeast of Brazil under an AI program. Materials, Methods & Results: Mares were initially selected based on their reproductive performance, the absence of clinical-reproductive alterations and adequate body condition score. Mares in diestrus were randomly distributed in three experimental conditions, received 5 mg of Dinoprost and were monitored daily for estrus detection. After estrus detection, ovaries were monitored by ultrasonography, in 12-h intervals, until the follicle reached 35 mm. At this time-point, ovulation was induced with 0.042 mg of Buserelin endovenously, with 3,000 IU hCG by an intramuscular shot, and control mares received 2 mL of saline solution, also by an intramuscular shot. Both hCG and Buserelin displayed similar efficiencies (P > 0.05) for induction of ovulation and that both agents were effective (P < 0.05) for such purpose, since greater percentages (P < 0.05) of induction on mares treated from those of the control. Moreover, the total number of ovulations in mares treated at the end of the experiment was not different (P > 0.05) from those found in the Control. All ovulations occurred within a 72-h period after treatment. It can be observed that in mares treated with hCG or Buserelin, ovulations occurred both in more mares (P < 0.05) and at earlier time-points than mares from the control. It is also possible to note that pregnancy was not different (P > 0.05) between hCG and Buserelin groups, and that pregnancy of mares treated with ovulation-inducing factors was similar to the control. Discussion: The majority of ovulations in mares occurred within initial 48-h after treatment for both hCG and GnRH, suggesting a similar potential for horse assisted reproduction. Both hCG and Buserelin are two commonly used agents for induction of ovulation in mares. As described here, the majority of ovulations occurred within initial 48-h after treatment, a fact which can be attributed to hCG and GnRH activity, since it can happen in intervals from 36 to 48-h after treatment. Pregnancy rates did not differ among groups. These results are under the working hypothesis that hCG and Buserelin would display similar efficiencies on pregnancy rates. Despite the understanding of hCG activity on induction of ovulation due to its high specificity toward LH receptors and results from a direct effect on diminishing estradiol concentration, increasing LH, and further inducing ovulation within 48-h after treatment. In contrast, Buserelin has a similar functional property but acts upon LH synthesis and its release. In conclusion, ovulation in mares can be induced with both hCG and Buserelin, and both ovulation-inducing agents do not affect pregnancy rates.